Effect of perlite on average specific cake resistance in filtration of first carbonatation sludge - To?rul, Hasan; Arslan, Nurhan (My University, 1996)
Vacuum fitration was applied at different temperatures and filtration pressures to determine the average specific cake resistance of mud obtained from the constant pressure filtration of 1st carbonatation sludge obtained from sugar factory. Average specific cake resistance as highly dependent on the filtration pressure, which indicates that 1st carbonatation sludge forms compressible cake. The cake compressibility coefficients at 70°C, 80°C and 85°C were calculated as 0.45. 0.45 and 0.50, respectively. Perlite was used as filter aid to increase filtration efficiency. The effects of the amount of precoating and body feed concentration on average specific cake resistance were also studied. The lowest average specific cake resistance was obtained with precoating-body feed technique.
1. Karbonatlama çamurunun süzülmesinde ortalama spesifik kek direncine perlitin etkisi
Keywords: 1st Carbonatation Sludge; Average Specific Cake Resistance; Filtration; Perlite